QTLs identification for nitrogen and phosphorus uptake-related traits using ultra-high density SNP linkage. (November 2019) - Fu, Youqiang; Zhong, Xuhua; Pan, Junfeng; Liang, Kaiming; Liu, Yanzhuo; Peng, Bilin; Hu, Xiangyu; Huang, Nongrong
Highlights: A total of 21 QTLs for nitrogen and phosphorus uptake-related traits distributed in 16 regions along 6 chromosomes were detected, with QTLs maximum explaining 8.19% of the phenotypic variation. Two QTL clusters including AGB, TNC, TPC and GNC were detected in the region bin 140 and bin 146 on the chromosome 2, the distance between the two clusters was only 4.1 cM. These genomic regions might be deployed for the simultaneous improving the use efficiency of nitrogen and phosphorus in rice breeding. Abstract: To understand the genetic basis of nitrogen and phosphorus uptake in the cultivated rice, quantitative trait loci (QTL) analysis for 7 nitrogen and phosphorus uptake-related traits including above-ground biomass (AGB), leaf colour value (SPAD) in heading stage, grain nitrogen concentration (GNC), grain nitrogen content of the plant, total nitrogen content (TNC), grain phosphorus concentration, total phosphorus content (TPC) were conducted using SNP markers in a F2 population derived from a cross between GH128 and W6827. A total of 21 QTLs for nitrogen and phosphorus uptake-related traits distributed in 16 regions along 6 chromosomes were detected using a high density genetic map consisting of 1582 bin markers, with QTLs maximum explaining 8.19% of the phenotypic variation. Nine QTLs (42.9% of total QTLs) were detected on chromosome 2. Among them, two QTL clusters including AGB, TNC, TPC and GNC were also detected in the region bin 140 and bin 146 on the chromosome 2. The distance between the two clusters was only 4.1 cM. The presence of QTL clusters has important significance and could be useful in molecular marker assisted breeding. These genomic regions might be deployed for the simultaneous improving the use efficiency of nitrogen and phosphorus in rice breeding.